Zmartwychwstanie Pańskie w norbertańskim rękopisie „Kontemplacyja męki i śmierci Chrystusa Pana [...]” (1662) - Kaczor-Scheitler, Katarzyna (Poznańskie Studia Teologiczne, 2017)
The subject of the article is the analysis of 17th century meditations about the Resurrection of Christ included in the manuscript collection of the Norbertine Sisters in Zwierzyniec. The reflection covers the traditions about the triumph of the glorified Lord, the women’s visit to the Lord’s Tomb, the announcement of the Resurrection to the women, Christ offering fish to his disciples, Christ’s meeting with Mary Magdalene and the disciples on their way to Emaus. The mode of presentation of these themes emphasizes a number of dogmas and truths of faith, mostly about the Resurrection of Christ and his divine nature. It is demonstrated in the article that the Norbertine texts were based not only on Gospels, but also on apocryphal sources and emblematic representations. The deliberations clarify that the author probably intended not only to report the course of events, but first of all to give a testimony of faith, to assert the real resurrection of the crucified Christ. An insight into the issue of the Resurrection of Christ in the light of biblical tradition and Old Polish literature is also offered.